Nature-derived epigallocatechin gallate/duck’s feet collagen/hydroxyapatite composite sponges for enhanced bone tissue regeneration - Kook, Yeon Ji (2018)
Scaffolds mimicking structural and chemical characteristics of the native bone tissues are critical for bone tissue engineering. Herein, we have developed and characterized epigallocatechin gallate/duck's feet collagen/hydroxyapatite (EGCG/DC/HAp) composite sponges that enhanced the bone tissue regeneration. The three-dimensional composite sponges were synthesized by loading various amounts (i.e. 1, 5 and 10 μM) of EGCG to duck feet derived collagen followed by freeze-drying and then coating with hydroxyapatite. Several measuremental techniques were employed to examine the properties of the as-fabricated composite sponges including morphology and structure, porosity, compressive strength, etc. and as well compared with pristine duck feet derived collagen. SEM observations of EGCG/DC/HAp sponges showed the formation of a highly porous collagen matrix with EGCG embodiment. The porosity and pore size of sponges were found to increase by high EGCG content. The compressive strength was calculated as 3.54 ± 0.04, 3.63 ± 0.03, 3.89 ± 0.05, 4.047 ± 0.05 MPa for 1, 5 and 10 μM EGCG/DC/HAp sponges, respectively. Osteoblast-like cell (BMSCs isolated from rabbit) culture and in vivo experiments with EGCG/DC/HAp sponges implanted in nude mouse followed by histological staining showed enhanced cell internalization and attachment, cell proliferation, alkaline phosphatase expressions, indicating that EGCG/DC/HAp sponges have ahigh biocompatibility. Moreover, highEGCG content in the EGCG/DC/HAp sponges have led to increased cellular behavior. Collectively, the 5 μM of EGCG/DC/HAp sponges were suggested as the potential candidates for bone tissue regeneration.